2020
DOI: 10.1017/s0031182020001304
|View full text |Cite
|
Sign up to set email alerts
|

Effect of essential oils on Leishmania amazonensis: a systematic review

Abstract: This systematic review investigated the evidence for the therapeutic potential of essential oils (EOs) against Leishmania amazonensis. We searched available scientific publications from 2005 to 2019 in the PubMed and Web of Science electronic databases, according to PRISMA statement. The search strategy utilized descriptors and free terms. The EOs effect of 35 species of plants identified in this systematic review study, 45.7% had half of the maximal inhibitory concentration (IC50) 10 < IC50 ⩽ 50 μg mL−1 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 73 publications
2
5
0
Order By: Relevance
“…This is in agreement with a recent study in Dublin, Ireland that 30% of stray dogs and 41% of stray cats were harbouring at least one parasite infection [34]. In fact, similar findings have been found worldwide [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50].…”
Section: Discussionsupporting
confidence: 93%
“…This is in agreement with a recent study in Dublin, Ireland that 30% of stray dogs and 41% of stray cats were harbouring at least one parasite infection [34]. In fact, similar findings have been found worldwide [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50].…”
Section: Discussionsupporting
confidence: 93%
“…Recently, Luna et al [ 4 ] demonstrated that in the absence of new effective drugs against Trypanosoma and Leishmania , many studies demanded the use of EOs. In particular, da Silva et al [ 21 ] reviewed the potential activity of EOs from 35 plant species against L. amazonensis , of which 45.7% had an IC 50 < 10 μg/mL. Our results, together with reports in the literature, corroborate the antikinetoplastid potential of EOs and could stimulate the development of these natural products as a source of new phytotherapeutics for leishmaniasis and trypanosomiasis treatment.…”
Section: Resultssupporting
confidence: 83%
“…An increasing number of studies regarding the activity of EOs are also concerned with human parasites of major medical importance, including antileishmanial, antitrypanosomal and antiplasmodial potentialities [55][56][57]. Nevertheless, studies have been generally performed on in-vitro cultures of parasites, which necessitates further in vivo studies using animal models to validate the antiprotozoal potential.…”
Section: Chemical and Pharmacological Overview Of Essential Oil From Cuban Plantsmentioning
confidence: 99%